On the lateral dose profile of 4He beams in water. (August 2017) - Embriaco, A.; Bellinzona, V.E.; Fontana, A.; Rotondi, A.
Highlights: A fast and accurate model for the lateral dose calculation of 4 He beams in water is presented. The exact description of electromagnetic interactions allows for a minimal number of parameters for the nuclear part. The achieved solution is stable and more accurate than the traditional multi-Gaussian approach. The results are compared with validated MC simulations and the standard parametrization. Abstract: Purpose: We investigate the possibility to improve the accuracy of the lateral dose profile for 4 He beams with a novel approach, by extending an already validated model for proton beams to heavier ions. Methods: The full Molière theory for the Coulomb multiple scattering is applied to the case of 4 He beams, with a complete separation of the electromagnetic and of the nuclear contributions in the calculation of the total dose. The latter is described with only three free parameters. Results: The accuracy of the results compared with Monte Carlo predictions already validated with experimental data is comparable with other studies at low energy, but improves by a factor 2 at high energy. In addition the found solution is more stable with respect to (multi-) Gaussian and other parameterizations. This result makes this method of interest for applications to Treatment Planning Systems (TPS) in ion beam therapy. Conclusions: We propose a model, named MONET α (MOdel of ioN dosE for Therapy for α ), for the calculation of the lateral dose of 4 He beams in water that allows fast and accurate dose calculations by requiring a small data base of parameters as input.